(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article presents the results of optimizing the parameters of the soil stacker of a machine designed for covering pomegranate bushes with soil, based on the method of mathematical planning of experiments. The optimization was conducted using a multi-factor experimental design, which allowed the determination of the most effective working parameters that ensure high-quality performance and minimal energy consumption.